2019
DOI: 10.1556/0806.46.2018.065
|View full text |Cite
|
Sign up to set email alerts
|

Changes in heterosis of maize (Zea mays L.) varietal cross hybrids after four cycles of reciprocal recurrent selection

Abstract: Two improved tropical maize composites, TZL COMP3 and TZL COMP4; representing complementary heterotic pools have been subjected to four cycles of reciprocal recurrent selection (RRS) for two decades to enhance varietal cross performance. The objectives of this study were to evaluate the effect of selection on genetic gain in heterosis for grain yield and other agronomic traits of these composites. Ten parental populations representing the C 0 to C 4 of each composite and their crosses plus a varietal check wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 19 publications
0
4
0
2
Order By: Relevance
“…However, origional population -C 0 showed least mean values and unproductive recital for yield related parameters with optimum and delayed plantings at both sites. Past studies also authenticated that improved populations revealed best performance and the highest grain yield than base population, which confirmed that might the feasible genes accumulated in the particular versions of the maize populations (Khamkoh et al, 2019;Kolawole et al, 2019). Significant impact of the recurrent selection cycles was observed on cob traits and grain yield, and the improved populations C 1 and C 2 executed better performance than maize base population (Ayiga-Aluba et al, 2015;Sohail et al, 2018;Sajjad et al, 2020a, b).…”
Section: Sajjad Et Almentioning
confidence: 69%
See 3 more Smart Citations
“…However, origional population -C 0 showed least mean values and unproductive recital for yield related parameters with optimum and delayed plantings at both sites. Past studies also authenticated that improved populations revealed best performance and the highest grain yield than base population, which confirmed that might the feasible genes accumulated in the particular versions of the maize populations (Khamkoh et al, 2019;Kolawole et al, 2019). Significant impact of the recurrent selection cycles was observed on cob traits and grain yield, and the improved populations C 1 and C 2 executed better performance than maize base population (Ayiga-Aluba et al, 2015;Sohail et al, 2018;Sajjad et al, 2020a, b).…”
Section: Sajjad Et Almentioning
confidence: 69%
“…Sin embargo, la población original -C 0 mostró los valores medios más bajos y un comportamiento improductivo para los parámetros de rendimiento relacionados con las siembras óptimas y tardías en ambos lugares. Estudios anteriores también demostraron que las poblaciones mejoradas revelaron el mejor rendimiento y la mayor producción de grano que la población base, lo que confirmó que los genes deseables pueden ser acumulados en versiones particulares de poblaciones de maíz (Khamkoh et al, 2019;Kolawole et al, 2019). Se observó un impacto significativo de los ciclos de selección recurrente en los rasgos de la mazorca y de rendimiento de grano, y las poblaciones mejoradas C 1 y C 2 demostraron un mejor rendimiento que la población base de maíz (Ayiga-Aluba et al, 2015;Sohail et al, 2018;Sajjad et al, 2020a, b).…”
Section: Sajjad Et Alunclassified
See 2 more Smart Citations
“…Least square mean were computed and separated using Fisher's least significant difference (LSD) test (p < 0.05). Mid-parent heterosis was calculated for all measured traits using the formula of Mather & Jinks (1971) and the student t-statistics was used to determine the statistical difference of F 1 hybrid means and the mid-parent according to Wynne et al (1970) and Kolawole et al (2019). Potence ratio was calculated according to Smith (1952) to determine the degree of dominance.…”
Section: Statistical Analyses and Estimationmentioning
confidence: 99%